Surgery for drug resistant partial epilepsy in children with focal cortical dysplasia: anatomical–clinical correlations and neurophysiological data in 10 patients. Issue 11 (14th November 2003) - Francione, S; Vigliano, P; Tassi, L; Cardinale, F; Mai, R; Lo Russo, G; Munari, C
Abstract : Objective: To analyse a population of children with focal cortical dysplasia operated on for drug resistant partial epilepsy, with emphasis on clinical features, seizure semiology, interictal and ictal EEG and stereo EEG findings, histological and topographical characteristics of the lesions, extension and localisation of cerebral excision, and its postoperative effect on seizure frequency. Methods: 10 patients were studied, aged between 26 months and 11 years (median 6 years). Magnetic resonance imaging (MRI) abnormalities were unilobar (temporal 3, frontal 2), bilobar (2), or multilobar (1); the two patients with negative MRI suffered from frontal seizures. Presurgical diagnostic steps varied in complexity and invasiveness depending on the anatomical/electrical/clinical features of each patient. In four patients they included only scalp video EEG monitoring, and in six, also invasive recordings using stereotactically implanted intracerebral electrodes. Surgery consisted of corticectomy plus lesionectomy in all cases. Results: 70% of the patients were seizure-free after a minimum postoperative follow up of 25 months. These included three patients with temporal lesions and four of seven patients with other lobar or multilobar extratemporal localisation. One patient had improvement in seizure control. Outcome was poor in multilobar patients, but a class Ia outcome was obtained in one case after partial lesionectomy associated with bilobar corticectomy. All patients showed developmental improvement. Conclusions: Analysis of the data in these patients allowed the production of an "anatomical-clinical concordance" list, which appeared to be correlated with the diagnostic steps performed. Carrying out a stereo EEG exploration in the most complex cases proved useful in defining the epileptogenic zone in extratemporal and multilobar epilepsies. Stereo EEG recordings facilitated a tailored resection of extralesional cortex.